2018
DOI: 10.3892/ol.2018.9122
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑96 expression induced by low‑dose cisplatin or doxorubicin regulates chemosensitivity, cell death and proliferation in gastric cancer SGC7901 cells by targeting FOXO1

Abstract: MicroRNA-96 (miR-96) is transcriptionally associated with the induction of chemoresistance following chemotherapy by targeting to FOXO1 mRNA at one of two predicted binding sites in its 3'-untranslated region sequence. The upregulation of miR-96 is associated with a high risk of chemoresistance. Nevertheless, the mechanism by which miR-96 is upregulated remains largely undefined. In the present study, the gastric cancer SGC7901 cell line was treated with different doses of the chemotherapeutic agents cisplatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Targeting the FOXO1/CEBPB/NF-κB/CCL20 axis in tumors may provide a novel potential therapeutic strategy for controlling CRC. MicroRNA-96 expression induced by low-dose cisplatin or doxorubicin regulates chemosensitivity, cell death, and proliferation in gastric cancer SGC7901 cells by targeting FOXO1 [52]. Piva et al showed that functional validation of the anaplastic lymphoma kinase signature identifies CEBPB as a critical target gene [53].…”
Section: Discussionmentioning
confidence: 99%
“…Targeting the FOXO1/CEBPB/NF-κB/CCL20 axis in tumors may provide a novel potential therapeutic strategy for controlling CRC. MicroRNA-96 expression induced by low-dose cisplatin or doxorubicin regulates chemosensitivity, cell death, and proliferation in gastric cancer SGC7901 cells by targeting FOXO1 [52]. Piva et al showed that functional validation of the anaplastic lymphoma kinase signature identifies CEBPB as a critical target gene [53].…”
Section: Discussionmentioning
confidence: 99%
“…Upregu- Extensive studies have shown that miR-96-5p is upregulated in various types of cancer, including bladder cancer, breast cancer, colorectal cancer, gastric cancer, and non-small-cell lung cancer, as well as HCC. 13,[22][23][24][25][32][33][34][35][36][37][38] It was also shown by in vitro analyses using corresponding cancer cell lines that miR-96-5p promotes proliferation and invasion and inhibits apoptosis, suggesting that it acts as an oncogenic miRNA. In contrast to these studies, downregulation of miR-96-5p has been reported repeatedly in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 95%
“…miR-96-5p was reported to promote gastric, prostate, and cervical cancers. 16,17 Additionally, miR-96-5p modulates cell proliferation, invasion, and migration in different diseases. 18,19 However, the role of miR-96-5p in wound healing has not been illustrated.…”
Section: Discussionmentioning
confidence: 99%